Tháng Năm 19, 2024

Rút gọn biểu thức sau \(\sqrt {{{\left( {a – b} \right)}^2}} – 3\sqrt {{a^2}} + 2\sqrt {{b^2}} \) với \(a < 0 < b\) A \( – 2a + b\) B \(3b – 2a\) C \(2a + 3b\) D \(a + b\)

Rút gọn biểu thức sau \(\sqrt {{{\left( {a – b} \right)}^2}} – 3\sqrt {{a^2}} + 2\sqrt {{b^2}} \) với \(a < 0 < b\)

A \( – 2a + b\)

B \(3b – 2a\)

C \(2a + 3b\)

D \(a + b\)

Hướng dẫn Chọn đáp án là: C

Phương pháp giải:

Áp dụng hằng đẳng thức \(\sqrt {{A^2}} = \left| A \right| = \left\{ \begin{array}{l}A\,\,\,khi\,\,\,A \ge 0\\ – A\,\,\,khi\,\,\,A < 0\end{array} \right..\)

Lời giải chi tiết:

\(\sqrt {{{\left( {a – b} \right)}^2}} – 3\sqrt {{a^2}} + 2\sqrt {{b^2}} = \left| {a – b} \right| – 3\left| a \right| + 2\left| b \right|\)

Vì \(a < 0 < b \Rightarrow \left\{ \begin{array}{l}a – b < 0\\a < 0\\b > 0\end{array} \right. \Rightarrow \left\{ \begin{array}{l}\left| {a – b} \right| = b – a\\\left| a \right| = – a\\\left| b \right| = b\end{array} \right.\)

\(\begin{array}{l} \Rightarrow \left| {a – b} \right| – 3\left| a \right| + 2\left| b \right| = b – a – 3\left( { – a} \right) + 2b\\ = b – a + 3a + 2b\\ = b – a + 3a + 2b\\ = 2a + 3b.\end{array}\)

Chọn C.